Mass and energy analysis of composite pellet process. (26th November 2018) - Purohit, Suneeti; Rhamdhani, Akbar; Brooks, Geoffrey
ABSTRACT: Composite pellet processes, such as ITmk3, are reported to have lower environmental emissions and increased energy efficiency compared to the blast furnace route. This paper proposes a mathematical model based on the mass and energy balance of the ITmk3 process following the basic principles of Rist diagrams. HSC Simulation has been used to calculate several process parameters such as the stoichiometric air requirement, air-preheating temperature and the off-gas composition of the composite pellet process for comparing to the Rist calculations. The Rist analysis suggests that the composite pellet process requires 7–14% of less carbon feed compared to the blast furnace. The heat loss from the composite pellet process has been estimated by utilising ITmk3 plant data and found to be in excess of 1.21 GJ. The heat demand of the composite pellet process at different degrees of post-combustion and heat recovery has also been reported.